2018
DOI: 10.1111/desc.12748
|View full text |Cite
|
Sign up to set email alerts
|

The malleability of executive function in early childhood: Effects of schooling and targeted training

Abstract: Executive function (EF), its importance for scholastic achievement and the question of whether or not EF is malleable, have become a topic of intense interest. Education or schooling is often seen as effective approaches to enhance EF due to the specific school-related requirements as compared to kindergarten or pre-school. However, no study to date has investigated whether targeted training focusing on those domains might be comparable with regular schooling in improving EF and fluid intelligence (Gf). The ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 86 publications
1
21
0
2
Order By: Relevance
“…Together, our findings of the effects of targeted cognitive training on EFs are in line with those of Zhang et al (2018), which showed that children had pronounced gains in the trained working memory and inhibitory control tasks. What is more important to us, however, is the fact that such training impacted more effectively children of low-SES, who study in public schools in Overall, our results support studies of children ranging from preschool to middle school, which suggest that low-SES children have a reduced performance on several tasks when compared to middle and high SES children (Noble et al, 2005;Farah et al, 2006).…”
Section: Near Transfer Efects and Sessupporting
confidence: 88%
“…Together, our findings of the effects of targeted cognitive training on EFs are in line with those of Zhang et al (2018), which showed that children had pronounced gains in the trained working memory and inhibitory control tasks. What is more important to us, however, is the fact that such training impacted more effectively children of low-SES, who study in public schools in Overall, our results support studies of children ranging from preschool to middle school, which suggest that low-SES children have a reduced performance on several tasks when compared to middle and high SES children (Noble et al, 2005;Farah et al, 2006).…”
Section: Near Transfer Efects and Sessupporting
confidence: 88%
“…For the studies reporting more than one intervention or control condition that met our inclusion criteria, we included more contrasts. If there were two or more eligible cognitive training programs, these were both included as compared with the control group (Thorell et al, 2009;Bergman Nutley et al, 2011;Howard et al, 2017;Romero López, 2018;Zhang et al, 2018). We did the same when there were multiple control conditions like an active and a passive control in the same study (i.e., Thorell et al, 2009;Peng et al, 2017;Pozuelos et al, 2019).…”
Section: Codingmentioning
confidence: 99%
“…Some studies have focused on the general effects of schooling on EFs (Brod et al, 2017;Zhang et al, 2019). Yet, very few studies have examined the association between specific curriculum-based activities at school (e.g., literacy activities) and EFs (Diamond et al, 2007;Burrage et al, 2008;Baker et al, 2015).…”
Section: Testing the Effects Of Coding On Efmentioning
confidence: 99%
“…Several studies have been conducted in the last few years to test the contribution of early intervention on the development of EFs (Liu et al, 2015;Traverso et al, 2015;Howard et al, 2018;Zhang et al, 2019). Other studies have explored the efficacy of ad hoc EF training programs (Kronenberger et al, 2011;Espinet et al, 2013;Grunewaldt et al, 2013;Hardy et al, 2016;Aarnoudse-Moens et al, 2018;Boivin et al, 2019;Zhang et al, 2019). For a review of intervention programs, see Diamond and Ling (2019).…”
Section: Introductionmentioning
confidence: 99%